Sensitization of Pancreatic Cancer Cells to Radiation by Cerium Oxide Nanoparticle-Induced ROS Production - Wason, Melissa S. (2012)
Side effect of radiation therapy (RT) remains the most challenging issue for pancreatic cancer treatment. In this report we determined whether and how cerium oxide nanoparticles (CONPs) sensitize pancreatic cancer cells to RT. CONP pretreatment enhanced radiation-induced reactive oxygen species (ROS) production preferentially in acidic cell-free solutions as well as acidic human pancreatic cancer cells. In acidic environments, CONPs favor the scavenging of superoxide radical over the hydroxyl peroxide resulting in accumulation of the latter whereas in neutral pH CONPs scavenge both. CONP treatment prior to RT markedly potentiated the cancer cell apoptosis both in culture and in tumors and the inhibition of the pancreatic tumor growth without harming the normal tissues or host mice. Taken together, these results identify CONPs as a potentially novel RT-sensitizer as well as protectant for improving pancreatic cancer treatment.